Effects of indium doping on the structural and optical properties of CdSe thin films deposited by chemical bath - Pérez González, A.M.; Arreola, I.V.; Tepantlán, C.S. (Revista Mexicana de Física, 2009)
Thin films of n-type CdSe have been grown on Corning glass substrate bychemical bath deposition, prepared with Sodium Seleno-Sulphate(Na$_{2}$SSeO$_{3})$, Cadmium Chloride (CdCl$_{2})$ and Indium Tri-Chloride(InCl$_{3})$, mixed in an aqueous environment. The effects of different Indoping concentrations have been investigated. X-ray diffraction spectra showthat at low In concentration only the CdSe lattice is present in thedeposited film, whereas CdIn$_{2}$Se$_{4 }$and InSe compounds are obtained athigher In concentrations. Optical properties have been calculated fromtransmission spectra and photoluminescence measurements. From transmissionspectra, the absorption coefficient and optical gap were obtained;photoluminescence spectra show band-band recombination from 10 K to roomtemperature.